A Retrospective Database Cohort Study Evaluating the Association Between Immune Suppressive Therapy and the Development of Cancer in Patients with Atopic Dermatitis Within UK Primary Care - Simon Wan Yau Ming; Yi Zhou; Mike Smith; Jay Were (European Medical Journal)
Introduction: First-line regular systemic treatment for atopic dermatitis (AD) in the UK consists of methotrexate, azathioprine, ciclosporin, or mycophenolate (immune-suppressive therapies [IST]). ISTs have been associated with malignancy, hence the need for evaluation for the relationship to the risk of developing cancer. Method: This retrospective cohort study utilising the Clinical Practice Research Datalink (CPRD) followed two cohorts with moderate or severe AD: one prescribed ISTs and one without. A total of 222,978 patients were included. The index date was the date of first IST prescription within primary care for the IST cohort, and the date of first potent topical steroid prescription from January 2001 to May 2021. Cohorts were propensity matched 1:1, resulting in 17,556 patients per cohort. Cox proportional hazard models were used to model the hazard of a cancer diagnosis. A secondary analysis was carried out on a restricted population, excluding patients with other comorbidities where ISTs were commonly prescribed. A further analysis explored the relation between the dose and the association with the risk of cancer. Results: Both the primary (hazard ratio: 1.01; 95% confidence interval: 0.94–1.08) and secondary (hazard ratio: 1.03; 95% confidence interval: 0.93–1.14) analyses did not show a significant difference in the hazard of a cancer code in the IST and non-IST cohorts. The exploratory dose–response analysis showed a higher risk of cancer associated with more prescriptions of IST per year. Conclusion: This study shows that amongst patients with moderate or severe AD, overall IST prescription in primary care is not associated with the onset of a cancer code. However, there is a trend with a higher risk of cancer coding with more prescriptions of IST.